'He is a New Man, a Proper Family Man': The Impact of a Specialist 'Family Wing' on the Quality of Family Relationships and Paternal Identity among Imprisoned Fathers. Issue 1 (16th October 2020) - CLANCY, ANNA; MAGUIRE, MIKE
Abstract: The article examines the operation and impact of a specialist wing in a male prison, which aims to repair and enhance family relationships. It outlines the damaging effects of parental imprisonment on children and on paternal identity, and explores whether, and how, residence on the wing and prisoners' joint participation with children and families in extended visits and family‐focused activities and interventions, mitigate such damage. The findings are overwhelmingly positive, demonstrating improvements in well‐being among children and family members, enhanced family relationships, and a stronger sense of paternal identity among prisoners. It is argued that these activities set in motion processes akin to those postulated by Burke (1991) as necessary for maintenance and renewal of identity: namely, the 'verification' of 'identity standards' through 'reflective appraisal' by key referent groups (here, families and children). There is also evidence that positive changes in prisoners quite frequently persist after release.